Political questions' jurisprudence and obiter dicta of the constitutional court: The institution of the president of the Republic of Lithuania according to the constitutional court's decision of 10 January 1998 - Kūris, Eugenijus (Politologija, 1998)
The essay examines in detail the Constitutional Court's decision of 10 January 1998. The Government had addressed the Constitutional Court in pursuit of an answer to the question of whether it had to resign after the new President was elected. As it could not address the Constitutional Court with that issue directly, it questioned the constitutionality of the Seimas resolution (10 December 1996) approving the Government's program for a period allegedly extending long after the presidential elections.It is shown that the issue investigated by the Constitutional Court was not only a legal but also a political question. Political questions are brought before constitutional courts in all legal traditions. The Supreme Court of the United States has developed a thorough (however contradictory) political question doctrine. This doctrine allows avoiding delegitimation of the Court's decisions in the eyes of public opinion, the media, etc. In the countries belonging to the European tradition of constitutional review, political questions usually do not form a distinct limiting doctrine. Nevertheless, in many Central and Eastern European countries such doctrines are allowed by their constitutions, stating that (constitutional) courts decide only questions of law. In Lithuania, it is established by the Constitution and reiterated by the Law on the Constitutional Court. In 1993-1996, the Constitutional Court had developed rudiments of political question doctrine, however not as a distinct one but as several separate limiting doctrines (those of standing, statute of limitations, sources of law, gaps in law, etc.). The decision of 10 January 1998 marks the radical turn to the direction of the positive political question doctrine.The Constitutional Court stated that the Government's program was a legal document, and that it was approved for a period of four years. In the article, it is proved that the program is a political document (however having legal significance), and that the four years period is the longest period for which the Government may function, although the Constitution foresees many instances in which this period may be shorter (resignation, vote of non-confidence, etc.).It was interpreted that, after the presidential elections, the Government (cabinet) was bound by the Constitution not to resign but only to "return" its powers (authorization) to the new President who, in his turn, had no right to propose to the Parliament for approval a candidacy of the Prime Minister other than the previous one. Thus, "returning" of powers was considered a version of the French Third Republic's demission de courtoisie. Reliance on the doubtful legal transplants in constitutional interpretation is seen as one of the principal weaknesses of the Constitutional Court's interpretation of the Constitution. It is demonstrated in the essay that the Constitutional Court's decision is not considered legitimate (however lawful) neither by lawyers' professional corporation nor by public opinion, and the reasons for that are supported by thorough analysis of the dicta. Moreover, the analysis of subtle wording of the new President's decrees allows foreseeing the tendency of delegitimation of dicta in the political process.
Keywords: -